The Insights on Perceived Price-Quality - Wangsa , Ignasius Heri Satrya (Universitas Prasetiya Mulya, 2011)
This research employs four theories; absolute and relative price differences (Theory-1), a “free” product (Theory-2), consumer perception of price unfairness (Theory-3), and consumer perception of price as an indicator of product quality (Theory-4). All of these are integrated and synthesizal in order to applicable provide an interpretation framework. Using Consistency Test and phenomenological approach, the author analyzes the participants’ responses around the issues of price and benefit to get some insights on perceived price-quality.